Proposed methodology for measurement, survey and assessment of vertical deformation of structures. Issue 3 (11th July 2016) - Ruiz-Jaramillo, Jonathan; Mascort-Albea, Emilio; Jaramillo-Morilla, Antonio
Abstract : Purpose: – Growing awareness of the importance of preserving the built environment has created an increasing demand for experts capable of performing building inspections to ensure a high level of preservation. Technical surveys include a set of procedures and tests that have become essential tools providing the necessary knowledge required for maintenance, preservation and improvement of buildings. The paper aims to discuss these issues. Design/methodology/approach: – Within this set of inspection techniques, this paper presents a method developed to produce vertical deformation plans from the levelling data obtained from different floors of a building. It also explains how to perform accurate levelling and an outcome analysis to provide displacement maps. Thus, based upon obtained measurements, it is possible to achieve 2D contour maps and three-dimensional (3D) surface mapping by means of specialized software that is typically used for cartographic and territorial analysis. Findings: – The developed methodology provides easier analysis of the deformation of buildings and structures. Consequently, the method produces relatively accurate outcomes that are sufficient to make a proper assessment that facilitates the diagnostic and decision-making process. The case studies analysed show the applicability and usefulness of the procedure. Originality/value: – This sustainable and non-destructive system is an essential instrument for providing valuable and useful information to the specialist. The 2D/3D graphical data displays enable easier analysis of survey results, also aiding comprehension of these results in the context of liability claims.